2011
DOI: 10.1007/s10529-011-0704-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a putative β-lactamase gene in the genome of Zymomonas mobilis

Abstract: Zymomonas mobilis ZM4 is resistant to β-lactam antibiotics but there are no reports of a β-lactam resistance gene and its regulation. A putative β-lactamase gene sequence (ZMO0103) in the genome of Z. mobilis showed a 55% amino acid sequence identity with class C β-lactamase genes. qPCR analysis of the β-lactamase transcript indicated a higher level expression of the β-lactamase compared to the relative transcript quantities in antibiotic-susceptible bacteria. The putative β-lactamase gene was cloned, expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Both ORFs contained ATG as start codon, which was preceded by a putative ribosome binding site (rbs). The identified rbs for end 1 and 2 matched with reported rbs of Zymomonas mobilis ethanologenic genes (Theberge et al 1992;Rajnish et al 2008) and β-1,4-endoglucanase of Bacillus pumilus strain (Lima et al 2005), respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Both ORFs contained ATG as start codon, which was preceded by a putative ribosome binding site (rbs). The identified rbs for end 1 and 2 matched with reported rbs of Zymomonas mobilis ethanologenic genes (Theberge et al 1992;Rajnish et al 2008) and β-1,4-endoglucanase of Bacillus pumilus strain (Lima et al 2005), respectively.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, similar growth inhibition was also observed in four ampicillin−resistant (AR) genes of ZMO0103 , ZMO0893 , ZMO1094 and the ZMO1650 knockout strain ZM4∆ARs. The previous study reported that ZMO0103 was a β−lactamase gene, which contains a 55% amino acid sequence identity with class C β−lactamase genes [ 20 ]. A higher expression level [ 30 , 34 , 35 , 36 ] of ZMO0103 in ZM4 may be ascribed to the absence of the AmpR that can inhibit the expression of ZMO0103 .…”
Section: Discussionmentioning
confidence: 99%
“…Although Z. mobilis is tolerant to ampicillin, only one work reported that ZMO0103 probably is an ampicillin−resistant gene, which reported the results of a heterologous protein expression and an enzymatic kinetic analysis [ 20 ]. The genome sequence of Z. mobilis ZM4 was published, and the genome annotation was further improved [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have earlier reported that Z. mobilis showed high level of resistance (in clinical standards) to β-lactam antibiotics, such as cephalexin, cephalosporin C, cephalothin, benzylpenicillin and penicillin V (Rajnish et al 2011). The cloning and expression of a β-lactamase gene from Z. mobilis B406 in Escherichia coli JM 109 has been reported (Mukundan et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The cloning and expression of a β-lactamase gene from Z. mobilis B406 in Escherichia coli JM 109 has been reported (Mukundan et al 1994). We have cloned, expressed, purified and characterized one of the β-lactamase (YP 161838) of Z. mobilis, in which the β-lactamase clone showed high level of resistance to ampicillin, benzylpenicillin, cephalexin and penicillin V (Rajnish et al 2011). We have also reported the homology based structural study of the β-lactam resistance determinants in Z. mobilis (Sheik Asraf et al 2012).…”
Section: Introductionmentioning
confidence: 99%